A novel user-based gesture vocabulary for conceptual design. Issue 150 (June 2021) - Vuletic, Tijana; Duffy, Alex; McTeague, Chris; Hay, Laura; Brisco, Ross; Campbell, Gerard; Grealy, Madeleine
Highlights: Vocabulary of user elicited gestures for conceptual design Significant repetition between the participant suggested gestures Evaluation confirms gestures are easy to perform Shape of the object being interacted with has an effect on some gestures Abstract: Research into hand gestures for human computer interaction has been prolific recently, but within it research on hand gestures for conceptual design has either focused on gestures that were defined by the researchers rather than the users, or those that were heavily influenced by what can be achieved using currently available technology. This paper reports on the study performed to identify a user elicited vocabulary of gestures for conceptual design, disassociated from the currently available technology, and its subsequent evaluation. The study included 44 product design engineering students (3 rd, 4 th year and recent graduates) and identified 1772 gestures that were analysed to build a novel gesture consensus set of vocabulary of hand gestures for conceptual design. This set is then evaluated by 10 other professionals, in order to generalise this set for a wider range of users and possibly reduce the need for training. The evaluation has shown that majority of gestures added to the vocabulary were easy to perform and appropriate for the activities, but that at the implementation stage the vocabulary will require another round of evaluation to account for the technology capabilities. The aim of this work is to create a starting point for a potential future system that could adapt to individual designers and allow them to use non-prescribed gestures that will support rather than inhibit their conceptual design thinking processes, akin to the developments that happened in hand writing recognition or predictive texting. Graphical abstract: Image, graphical abstract